Clinical presentation of pili torti - Case report - Yang, Jeane Jeong Hoon (An Bras Dermatol, 2015)
Pili torti also known as ‘twisted hairs’ (Latin: pili=hair; torti=twisted) is a rare, congenital or acquired clinical presentation, in which the hair shaft is flattened at irregular intervals and twisted 180º along its axis. It is clinically characterized by fragile, brittle, coarse and lusterless hairs, due to uneven light reflection on the twisted hair surface. Pili torti may be associated with neurological abnormalities and ectodermal dysplasias. There is no specifi c treatment for this condition, but it may improve spontaneously after puberty. We report a case of pili torti in a child who presented fragile, brittle, diffi cult to comb hair. The patient had no comorbidities.